Clinical yield of magnetoencephalography distributed source imaging in epilepsy: A comparison with equivalent current dipole method. Issue 1 (11th October 2017) - Pellegrino, Giovanni; Hedrich, Tanguy; Chowdhury, Rasheda Arman; Hall, Jeffery A.; Dubeau, Francois; Lina, Jean‐Marc; Kobayashi, Eliane; Grova, Christophe
Abstract: Objective: Source localization of interictal epileptic discharges (IEDs) is clinically useful in the presurgical workup of epilepsy patients. It is usually obtained by equivalent current dipole (ECD) which localizes a point source and is the only inverse solution approved by clinical guidelines. In contrast, magnetic source imaging using distributed methods (dMSI) provides maps of the location and the extent of the generators, but its yield has not been clinically validated. We systematically compared ECD versus dMSI performed using coherent Maximum Entropy on the Mean (cMEM), a method sensitive to the spatial extent of the generators. Methods: 340 source localizations of IEDs derived from 49 focal epilepsy patients with foci well‐defined through intracranial EEG, MRI lesions, and surgery were analyzed. The comparison was based on the assessment of the sublobar concordance with the focus and of the distance between the source and the focus. Results: dMSI sublobar concordance was significantly higher than ECD (81% vs 69%, P  < 0.001), especially for extratemporal lobe sources (dMSI = 84%; ECD = 67%, P  < 0.001) and for seizure free patients (dMSI = 83%; ECD = 70%, P  < 0.001). The median distance from the focus was 4.88 mm for ECD and 3.44 mm for dMSI ( P  < 0.001). ECD dipoles were often wrongly localized in deep brain regions. Conclusions: dMSI using cMEM exhibited better accuracy. dMSI also offered the advantage of recovering more realistic maps of the generator, which could be exploited for neuronavigation aimed at targeting invasive EEG and surgical resection. Therefore, dMSI may be preferred to ECD in clinical practice. Hum Brain Mapp 39:218–231, 2018 . ©2017 Wiley Periodicals, Inc.